Promoting Nature-Based Tourism for Management of Protected Areas and Elephant Conservation in Sri Lanka - World Bank (Washington, DC, 2013)
Sri Lanka's ten-year development framework aims at accelerating economic growth while ensuring a path of sustainable development and prioritizing conservation of the country's natural heritage. It is in this context that this policy note seeks to examine the scope for enhancing protection of Sri Lanka's natural assets through nature based tourism as an instrument for conservation with a specific focus on elephant conservation. This study identifies development opportunities that increase tourism revenues and offers an assessment of the human/elephant conflict, which is the primary impediment to long term elephant conservation.